Intraoperative Colonoscopy During Colorectal Surgery Does Not Increase Postoperative Complications: An Assessment From the ACS-NSQIP Procedure-targeted Cohort. Issue 4 (August 2021) - Tatar, Cihad; Benlice, Cigdem; Rencuzogullari, Ahmet; Church, James; Ozuner, Gokhan; Liska, David; Steele, Scott R.; Gorgun, Emre
Abstract : Intraoperative colonoscopy (IOC) is an adjunct in colorectal surgery to detect the location of the lesions and assessing anastomotic integrity. The authors aimed to evaluate the safety and feasibility and postoperative morbidity of IOC in left-sided colectomy patients for colorectal cancer. Patients undergoing elective left-sided colectomy without any proximal diversion for colorectal cancer between 2013 and 2016 were reviewed from the American College of Surgeons National Surgical Quality Improvement Program procedure-targeted database. Demographics, comorbidities, short-term outcomes, and postoperative morbidity of patients were evaluated. A total of 8811 patients were identified and IOC was performed for 1143 (12.97%) patients. There was no significant difference in postoperative complications between the IOC and non-IOC groups. Patients with IOC had shorter total hospital length of stay. The use of IOC does not adversely affect short-term outcomes after colorectal resections. Surgeons may utilize IOC liberally for left-sided colorectal resections.